2007
DOI: 10.1093/europace/eul130
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of mechanical transvenous dilation and location of areas of adherence in patients undergoing coronary sinus lead extraction

Abstract: Our study suggests that CS leads, after medium-term implantation, can be effectively and safely removed using MD with polypropylene sheaths, in the case of unsuccessful LT. No pre-operative elements predictive of LT failure could be identified. Areas of adherence were rarely located in the CS or its tributaries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 7 publications
5
44
1
Order By: Relevance
“…Of the four cases requiring laser extraction, three required laser application within the CS (1 proximal CS and 2 distal CS) with no complications reported. Bongiorni et al [25] reported on a larger cohort of 37 CS lead extractions. The age of the CS leads in this study was 19.5±16.5 months.…”
Section: Coronary Sinus Leadsmentioning
confidence: 99%
“…Of the four cases requiring laser extraction, three required laser application within the CS (1 proximal CS and 2 distal CS) with no complications reported. Bongiorni et al [25] reported on a larger cohort of 37 CS lead extractions. The age of the CS leads in this study was 19.5±16.5 months.…”
Section: Coronary Sinus Leadsmentioning
confidence: 99%
“…Furthermore, as showed by venography also in the present case, this particular lead is often associated with a signifi cant thrombotic reaction with chronic occlusion of the CS vein branch and lead entrapment [5]. Cronin et al described CS vein occlusion and fi brotic adhesions between polyurethane lobes and CS endothelium as an important mechanism making transvenous lead extraction extremely diffi cult and preventing implantation of a new lead in the same CS vein branch [6].…”
Section: Discussionmentioning
confidence: 49%
“…While deployment and removal of such lead has been reported to be achieved successfully in the acute setting [3], information regarding both function of the fi xation mechanism and easiness of lead removal in the long-term are limited [3]. As shown previously [5] transvenous extraction of the StarFix™ lead may be extremely challenging requiring complex mechanical dilatation techniques in order to completely remove it without fracturing and dislodgement of the polyurethane lobes.…”
Section: Discussionmentioning
confidence: 99%
“…The largest study to date by Bongiorni et al. , reported on 37 patients. The longest CS lead had been in situ for 84 months.…”
Section: Discussionmentioning
confidence: 99%